2010
DOI: 10.1007/s10479-010-0707-0
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking curriculum-based course timetabling: formulations, data formats, instances, validation, visualization, and results

Abstract: We propose a set of formulations for the Curriculum-Based Course Timetabling problem, with the aim of "capturing" many real-world formulations, and thus encouraging researchers to "reduce" their specific problems to one of them, gaining the opportunity to compare and assess their results. This work is accompanied by a web application that maintains all the necessary infrastructures for benchmarking: validators, data formats, instances, reference scores, lower bounds, solutions, and visualizers. All instances p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 20 publications
1
57
0
Order By: Relevance
“…As a potential example, the structure of the PSTP is similar to those used in the ITC2007 course timetabling track, [35], and so this suggests that ICMA be also tested on this domain. We note that [55] uses an integer programming method (as opposed to a metaheuristic) but that it does exploit the given grouping structure of the events in the problem; thus re-iterating the general potential utility of structure exploitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a potential example, the structure of the PSTP is similar to those used in the ITC2007 course timetabling track, [35], and so this suggests that ICMA be also tested on this domain. We note that [55] uses an integer programming method (as opposed to a metaheuristic) but that it does exploit the given grouping structure of the events in the problem; thus re-iterating the general potential utility of structure exploitation.…”
Section: Resultsmentioning
confidence: 99%
“…Two tracks of this competition covered two different CTPs: post enrollment course timetabling and curriculum based course timetabling and a third track covered the examination timetabling problem. Bonutti et al [35] describe formulations for the curriculum based course timetabling problem introducing new problem instances additional to the ones provided in the competition. The best performing curriculum based course timetabling and examination timetabling approach turned out to be a multi-stage hybrid algorithm as described in Müller (2009) [36].…”
Section: High-school Course Timetabling and Metaheuristic Solutionsmentioning
confidence: 99%
“…The set of heuristics are supposed to make some progressive moves in datasets. This article is expansion of research work published by [1] and shown the functionally of four more important low level heuristics (LLH 8 , LLH 9 , LLH 10 , LLH 11 ).…”
Section: Introductionmentioning
confidence: 90%
“…These are real cases taken mainly from the University of Udine which were used for the International Timetabling Competition in 2007-08 (ITC2007) [47]. Since the objective of the timetabling problem of the FEB Campus Brussels is novel in the literature (minimization of the student flow between classrooms), we do not intend to Table 3: Description of the instances tested.…”
Section: Data From the Literaturementioning
confidence: 99%